Effectiveness of mindfulness-based stress reduction program on depression and adherence to treatment in female coronary heart patients - Kolahi, Parisa; Salehi, Mahdie; Madahi, Mohammad Ebrahim; Sepahmansour, Mozhgan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study was conducted with the aim of determining the effectiveness of the mindfulness-based stress reduction program on depression and adherence to treatment in coronary heart patients. Methods: The present study was conducted as a semi-experimental type of pre-test-post-test and follow-up with a control group with measurement at the baseline after the intervention and 3-month follow-up with the control group. The number of 52 female patients diagnosed with coronary artery disease from among the patients referred to Hazrat Fatemeh (S) specialized polyclinic (Social Security Organization) located in Urmia city from September to December 2019 and randomly selected to the group Experiment (mindfulness-based stress reduction program (n=26) and control (n=26) were assigned. All participants completed the demographic questionnaire, Beck et al.'s depression questionnaire (1996) and Moriski, Eng and Wood's (2008) treatment adherence questionnaire in three stages. Mindfulness-based stress reduction program was conducted in eight weekly sessions based on Mochari et al.'s training package (2014). The research was analyzed using multivariate repeated measures analysis of variance as well as Tukey's follow-up tests. Results: The results of the present study showed that the stress reduction program based on mindfulness on depression (F=561.08, P